PANDEMIA A FUNKCJONOWANIE JEDNOSTEK SAMORZĄDU GMINNEGO ZADŁUŻONYCH W PARABANKACH – PRZYPADEK GMINY RACIECHOWICE - Balcerek-Kosiarz, Marta (Polityka i Społeczeństwo, 2021)
The aim of the article is to present the influence of pandemic, which contributes to changes in the scope of the delivery of public services by local governments. An interesting example are local governments, which have increased their financial debt in spite of their financial recovery programmes. These local governments were forced to change their public service strategies and their management in the sphere of select organizational and legal forms. The article presents the proposal of the public service delivery on the example of the Raciechowice municipality, in the Małopolskie voivodship, which in 2020 reached the highest debt level in Poland. The financial condition of the Raciechowice municipality is compared with the Ostrowice municipality, which was abolished on January 1, 2020 by including its territory into Drawsko Pomorskie. The core conclusion of the study is the fact that the delivery of public services by budgetary units contributes to the increase of the financial debt of the Raciechowice municipality. The decisions of central authorities, which instead of implementing long-term solutions during the pandemic availed themselves of emergency aid tools, also impact the increase in the budgetary deficit. This resulted in the necessity of finding additional resources on the part of local government units and in consequence led to the growth of the non-bank financial intermediary market.